2018
DOI: 10.7203/jo3t.2.3.2018.11286
|View full text |Cite
|
Sign up to set email alerts
|

Ozone therapy in idiopathic carpal tunnel syndrome. Biochemical, neurophysiological and clinical aspects.

Abstract: Purpose. Idiopathic Carpal Tunnel Syndrome (CTS) is the most common entrapment neuropathy; however few and only retrospective studies have been found in search engines about Ozone Therapy. The aim of this paper was to evaluate clinical and neurophysiological outcome following Ozone Therapy in CTS. We focused the attention on the evidences concerning the role of Subsynovial Connective Tissue (SSCT) in the pathogenesis of CTS and the ozone pre-conditioning effects linked to pain and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In another more recent uncontrolled study, sensory nerve conduction and motor distal latency along with symptom severity (BCTQ questionnaire) were improved after eight sessions of O 2 -O 3 injections. [ 12 ] Contrary to these findings, the present study showed no significant changes in the electrodiagnostic and ultrasonographic parameters, although it should be noted that we used a single dose of O 2 -O 3 injection. Bahrami et al[ 1 ] compared the effectiveness of the single dose of O 2 -O 3 therapy against a control group (volar splint for eight weeks).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In another more recent uncontrolled study, sensory nerve conduction and motor distal latency along with symptom severity (BCTQ questionnaire) were improved after eight sessions of O 2 -O 3 injections. [ 12 ] Contrary to these findings, the present study showed no significant changes in the electrodiagnostic and ultrasonographic parameters, although it should be noted that we used a single dose of O 2 -O 3 injection. Bahrami et al[ 1 ] compared the effectiveness of the single dose of O 2 -O 3 therapy against a control group (volar splint for eight weeks).…”
Section: Discussioncontrasting
confidence: 99%
“…[ 10 , 11 ] Local injections have shown to be beneficial in mild to moderate cases, and there are promising results with corticosteroids (CS), progesterone, and platelet-rich plasma. [ 12 ] Local injection of CS is usually preferred in mild to moderate cases refractory to other modalities. There is often a rapid and significant improvement; however, it may not last in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Elawamy et al demonstrated that both intracarpal ozone or methylprednisolone reported advantageous impacts upon CTS in people with SSC; nonetheless, ozone relieves pain, enhances the hand functioning, decreases the duration and frequency of Raynaud’s attacks, declines the size of ulceration, and improves median nerve conduction study over the 6-month follow-up [ 132 ]. Rascaroli et al found slight improvements in sensory and motor parameters after ozone therapy, and Bahrami et al showed improvement of median sensory nerve action potential latency, compared to the pre-treatment level in both groups (one group treated with wrist volar splint alone, the other group treated with ozone injection and splint) [ 133 , 134 , 135 , 136 ]. The nature of the fibrotic expression in SSc people with CTS seemed to be significantly associated with gene upstream for Col1 and Col3, TGF-β, and SMAD3 in CTS fibroblasts [ 137 , 138 ].…”
Section: Oxygen-ozone and Rheumatic Diseasesmentioning
confidence: 99%
“…Recent studies have recommended local ozone therapy in some musculoskeletal conditions (70,71). Rascaroli et al showed that neurophysiological and functional parameters after O2-O3 treatment were improved significantly more than the motor and sensory nerve conduction parameters (72). The best clinical improvements were found in mild and moderate CTS groups (72).…”
Section: Ozone Injectionmentioning
confidence: 99%
“…Rascaroli et al showed that neurophysiological and functional parameters after O2-O3 treatment were improved significantly more than the motor and sensory nerve conduction parameters (72). The best clinical improvements were found in mild and moderate CTS groups (72). Although ozone therapy is a safe and low-cost method with some promising outcomes in patients with mild to moderate CTS, at least for short-term (70), further studies are needed in the future.…”
Section: Ozone Injectionmentioning
confidence: 99%